Promotional Performance, Personal Performance and Process Performance Impact on Increasing Consumer Satisfaction - Pebi Kurniawan; Ali Jufri (Dinasti International Journal of Education Management And Social Science, 2022)
The purpose of this study was to determine and analyze: (1) Promotion; (2) Personnel; (5) Process; (3) Consumer Satisfaction and (4) The Influence of Promotion Performance, Personnel, Process Performance on Micro Credit Customer Satisfaction at Bank BJB Bandung City. The research method used in this research is a descriptive survey and an explanatory survey, the unit of analysis in this study is the Micro Credit Customers at Bank BJB Bandung City with a sample of 50 people. The type of investigation is causality, and the time horizon in this study is cross-sectional. Based on the results of the study, it was found that the promotion performance according to Micro Credit Customers at Bank BJB Bandung City was generally not good; Personnel performance according to Micro Credit Customers at Bank BJB Bandung City is generally good and Process Performance according to Micro Credit Customers at Bank BJB Bandung City is generally not good, Micro Credit Customer Satisfaction at Bank BJB Bandung City is currently considered good. Promotion Performance, Personnel Performance and Process Performance have an effect on Micro Credit Customer Satisfaction at Bank BJB Bandung City. Because Personal affects customer satisfaction dominantly, then at Bank BJB Bandung City must maintain conditions so that the satisfaction of Micro Credit Customers at Bank BJB Bandung City remains consistent, so that customer satisfaction is formed strongly and deeply rooted.